The rocky road to the top. Why talent needs trauma - Collins, D.; MacNamara, A. (Sports Medicine, 2012)
The increasingly well funded and high-tech world of talent development (TD) represents an important investment for most sports. Reflecting traditional concepts of challenge and focus, the vast majority of such systems expend a great deal of effort maximizing support to the young athletes and trying to counter the impact of naturally occurring life stressors. In this article, we suggest that much of this effort is misdirected; that, in fact, talented potential can often benefit from, or even need, a variety of challenges to facilitate eventual adult performance. Our argument is built on evidence that such challenges are more common in athletes who reach the top, together with a critical consideration of the modus operandi and impact of psychological/character-focused interventions such as mental toughness and resilience. In conclusion, we explore some implications for the design and conduct of optimum academies and TD environments.